Arbitrating and Mediating Disputes : Benchmarking Arbitration and Mediation Regimes for Commercial Disputes Related to Foreign Direct Investment - Pouget, Sophie (World Bank, Washington, DC, 2014)
An effective commercial arbitration regime matters for foreign investors. It gives parties the autonomy to create a dispute resolution system tailored to increasingly complex disputes. Foreign investors view arbitration as a way to mitigate risks by providing legal certainty on enforcement rights, due process, and access to justice. The Arbitrating and Mediating Disputes indicators assess the legal and institutional framework for commercial arbitration, mediation, and conciliation regimes in 100 economies. All surveyed economies recognize arbitration as a tool for resolving commercial disputes and only nine economies have not acceded to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. In the Arbitrating and Mediating Disputes indicators, High Income OECD and Eastern Europe and Central Asia are the regions that reformed their laws on alternative dispute resolution the most between 2011 and 2012. The data also show that, globally, arbitration proceedings take 326 days on average, while recognition and enforcement proceedings of foreign arbitral awards take 557 days on average. The Arbitration and Mediating Disputes indicators are significantly correlated with perception data on the importance of alternative dispute resolution, as well as other measures such as total foreign direct investment inflows and inflows per capita, the Doing Business 2013 Enforcing Contracts data, the World Bank Group's Governance Indicators, the World Economic Forum's Global Competitiveness Indicators, and the Multilateral Investment Guarantee Agency's World Investment and Political Risk data. The paper concludes by identifying several opportunities for improvement, such as greater flexibility for domestic arbitration regimes, faster arbitration proceedings, and better domestic court capabilities.